KELAYAKAN FUNGSI KONTROL JEMBATAN TIMBANG STUDI KASUS JEMBATAN TIMBANG KULWARU - , TEGUH PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The movement of freight traffic from and to Yogyakarta is very high. To support it then takes planning facilities and good transport infrastructure. Good planning can begin to maximize the control function to transport goods through the weighbridge. In the presence of weighbridge we can obtain the total weight of freight, transport excess weight, the type of goods being transported as well as the purpose of the distribution of goods. This study aims to determine the feasibility of weighbridge control facilities, heavy freight vehicles were recorded as well as cargo freight vehicles axis. Research sites located in Kulwaru Weigh Bridge located on Highway Wates - Purworejo. Weighbridge used is fixed by the type of Deep Pit. In accordance with the Decree of the Minister of Transportation (KM 5/1995, on the Implementation of Vehicle Weighing On the Road) location of the study have the building operational support facilities